A Framework for Implementing Flexible Project-Based Learning for Computing Education in Resource-Constrained Environments: A Case Study of the Namibia University of Science and Technology - Maravanyika, Munyaradzi (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Project-based and problem-based learning (PBL) has gained recognition as an effective pedagogical method for developing essential for employability skills. However, implementing PBL in resource-constrained environments poses significant challenge in these environments due to the limited infrastructure and institutional barriers (Okai-Ugbaje et al., 2022). This paper introduces the Flexible Project-Based Learning (FPBL) framework designed to facilitate the adoption in such environments though a three-tiered approach: the Basic Tier (minimal resources), Standard-Tier (moderate resources) and Advanced-Tier (comprehensive resources). Each layer incorporates Aristotle’s four causes as structural pillars. Prelimary results from a case study at the Namibia University of Science and Technology involving focus groups with faculty (N = 5), industry stakeholders (N = 15), student representatives (N = 2) and administrative support staff (N = 4). Preliminary results from a case study at the Namibia University of Science and Technology (NUST) indicate that access to industry-grade infrastructure, partnerships, and readiness are essential for effective PBL implementation. The framework offers a possibly scalable solution for computing education in resource- constrained environments.